Impact of debris cover on glacier ablation and atmosphere–glacier feedbacks in the Karakoram - Collier, E.; Maussion, F.; Nicholson, L. I.; Mölg, T.; Immerzeel, W. W.; Bush, A. B. G. (The Cryosphere, 2015)
The Karakoram range of the Hindu-Kush Himalaya is characterized by both extensive glaciation and a widespread prevalence of surficial debris cover on the glaciers. Surface debris exerts a strong control on glacier surface-energy and mass fluxes and, by modifying surface boundary conditions, has the potential to alter atmosphere–glacier feedbacks. To date, the influence of debris on Karakoram glaciers has only been directly assessed by a small number of glaciological measurements over short periods. Here, we include supraglacial debris in a high-resolution, interactively coupled atmosphere–glacier modeling system. To investigate glaciological and meteorological changes that arise due to the presence of debris, we perform two simulations using the coupled model from 1 May to 1 October 2004: one that treats all glacier surfaces as debris-free and one that introduces a simplified specification for the debris thickness. The basin-averaged impact of debris is a reduction in ablation of ~ 14 %, although the difference exceeds 5 m w.e. on the lowest-altitude glacier tongues. The relatively modest reduction in basin-mean mass loss results in part from non-negligible sub-debris melt rates under thicker covers and from compensating increases in melt under thinner debris, and may help to explain the lack of distinct differences in recent elevation changes between clean and debris-covered ice. The presence of debris also strongly alters the surface boundary condition and thus heat exchanges with the atmosphere; near-surface meteorological fields at lower elevations and their vertical gradients; and the atmospheric boundary layer development. These findings are relevant for glacio-hydrological studies on debris-covered glaciers and contribute towards an improved understanding of glacier behavior in the Karakoram.